Responsibility of Child Offenders in Theft Offences in Islamic and Civil Laws - Aziz, Norjihan Ab; Che Ramli, Nur Najaa Syairah (Kanun: Jurnal Undang-undang Malaysia; Vol 35 No 2 (2023): Kanun: Jurnal Undang-undang Malaysia Volume 35 Number 2 July 2023, 2023)
Theft is a serious crime, be it in Islamic criminal law or civil law. Offenders who commit theft, according to the traditional justice system, must be held accountable through punishment. Children who have reached the minimum age of criminal liability, should they commit the offence of theft, are also not exempted. However, they cannot be judged like adult offenders. Islamic Law exempts children from hudud punishment for the crime of theft, but can be held responsible through the punishment of takzir. In Malaysia, child offenders who are involved in the crime of theft are governed by the Child Act 2001, in which they can be punished if convicted. The responsibility of child offenders in Malaysia is limited to the court order or punishment decided by the Court for Children only. However, the United Nations Convention on the Rights of the Child encourages member states to resolve minor criminal offences through the restorative justice process to enable child offenders to be held directly accountable to victims. For example, the United Kingdom and Brunei have allowed child offenders to be held accountable for offences committed based on the theory of restorative justice. This study examines how child offenders can be held responsible for victims based on Islamic and civil laws and their application in selected countries, as well as in Malaysia. This study suggests that the Child Act 2001 be amended to allow child offenders to be held directly responsible for victims through the restorative justice process. This study uses doctrinal method by referring to primary and secondary sources found in the library such as legal provisions, decided cases, books, journal articles, and others. Keywords : Child offenders, theft, restorative justice, criminal responsibility, punishment, child law Full text : PDF